ATTRACTION OF CULINARY TOURISM DESTINATIONS TO PROMOTE SUSTAINABILITY DEVELOPMENT DURING THE PANDEMIC - Agustina Multi Purnomo (Profetik: Jurnal Komunikasi, 2022)
Culinary tourism had the most extensive product portfolio and was one of the tourism sectors most affected by the pandemic in Indonesia. The website was a specific communication tool for promoting tourism. The study objective was to examine how the government's promotion of culinary tourism in official website content strengthens the sustainability of culinary tourism development during the pandemic. This study used qualitative content analysis on the official tourism promotion website of the Indonesian government, namely https://www.indonesia.travel. Two hundred twenty-four articles on the "Culinaries'' and "Culinaries & Wellness" links were analyzed in seven data groups and 17 keywords. The placement and number of keyword analysis on the website found that tourism promotion had identified culinary resources but not enough to promote culinary as a tourist attraction. Business actors with small capital have not been promoted adequately, and promotion has not offered virtual culinary tour packages and online purchase messages sufficiently. It was concluded that the promotion of culinary tourism still required improvement to strengthen it’s sustainability during the pandemic. The government must promote culinary tourism by increasing the messages specifically for culinary tourism, information on culinary tourism attractions, business actors, local food, small-capital business actors, supporting online promotion, and integrating culinary tourism into other tours.